Sistem Ekonomi Sosialisme Pasar - Gilang Rizki Aji Putra (ADALAH, 2020)
Abstract:Economy plays a very important role in human life. During its development, various methods or systems can be used to solve it. So far, there are three systems of economic development, namely capitalism / liberalism, socialism and Islam. Those are the questions that will be discussed in this scientific paper. By examining how government participation in development, the method used is descriptive analysis of the three systems. As a conclusion based on this description, it can be said that capitalism is a social system based on the recognition of individual rights. This includes property rights, where all ownership is private property. In other words, capitalism is an economic system that can fully control capital, or investors can use all types of capital. This includes commodities that are used to produce other commodities. The government or the contracting country must not interfere in economic development. The government only has the authority to formulate regulations regarding tax obligations for economic developers. Tax revenue will be used for the national interest, especially to fulfill its obligations for the welfare of the people.Keywords: Socialism, Karl Marx and Economics